THROUGHPUT-NORMALIZED METHANE EMISSION THRESHOLDS FOR DIAGNOSING ROD PACKING SEAL FAILURE IN RECIPROCATING COMPRESSORS - Rimelman, Ethan Cole, author; Hodshire, Anna L., advisor; Shonkwiler, Kira, committee member; Olsen, Dan, committee member (Colorado State University. Libraries, 2026)
Reducing the atmospheric concentration of greenhouse gases demands accurate quantification of methanesources. Compressors in the oil and gas industry generate significant emissions that often depend on the condition of the equipment. Estimating leak sources across different operational states provides a basis for assessing maintenance urgency. Traditional emission factors assign a single rate regardless of compressor size, but emission magnitudes are not necessarily proportional to the amount of gas a given unit processes. Using a throughput normalized approach captures the dependency of emissions from reciprocating compressors with their rated power. Using data from Zimmerle et al.’s Gathering Emission Factor (GEF) field study of gathering and boosting stations, it is shown that compressors below 1000 HP exhibit a median rod packing fractional loss approximately 3.7 times that of larger units, with a larger difference of roughly 57 times for blowdown vent emissions. These differences show that smaller compressors lose a greater fraction of throughput across both emission sources. Applying a log-log linear fit to the GEF data, a framework is established for assessing and diagnosing rod packing seal failure. Within this model, the fractional-loss threshold indicating likely seal failure (95th percentile) is approximately 0.23% for a 350 HP unit, representative of a production-scale vapor recovery compressor, and 0.044% for a 1000 HP unit. A model for estimating throughput normalized emissions is valuable for modeling and regulatory functions. For mitigating emissions, policy could adopt a framework that assigns maintenance actions dynamically, with thresholds based on associated engine power.
Keywords: emissions; reciprocating; compressors; throughput; methane